Morphological and molecular identification of leptocephali of Taiwanese duckbill conger, Gavialiceps taiwanensis (Chen & Weng, 1967) (Family Congridae) - Lin, Chien-Ting; Ho, Hsuan-Ching (Zootaxa, 2018)
The leptocephali of the Taiwanese duckbill conger are described in detail for the first time based on specimens collected from near the type locality. Morphological and molecular features are employed to compare the leptocephali, juveniles and adults. The morphology of leptocephali can be divided into three stages, with clear metamorphosis of the jaw structure and morphometric proportions. Detailed description and comparison of each leptocephalic stage, juveniles and adults, and the ontogenetic changes of leptocephali are provided.